Cue-induced striatal activity in frequent cannabis users independently predicts cannabis problem severity three years later. (February 2016) - Vingerhoets, WAM; Koenders, L; van den Brink, W; Wiers, RW; Goudriaan, AE; van Amelsvoort, T; de Haan, L; Cousijn, J
Cannabis is the most frequently used illicit drug worldwide, but little is known about the mechanisms underlying continued cannabis use. Cue-reactivity (the physical, psychological, behavioural and neural reaction to substance-related cues) might be related to continued cannabis use. In this 3-year prospective neuroimaging study we investigated whether cannabis cue-induced brain activity predicted continued cannabis use and associated problem severity 3 years later. In addition, baseline brain activations were compared between dependent and non-dependent cannabis users at follow-up. Analyses were focussed on brain areas known to be important in cannabis cue-reactivity: anterior cingulate cortex, orbitofrontal cortex, ventral tegmental area, amygdala and striatum. At baseline, 31 treatment-naive frequent cannabis users performed a cue-reactivity functional magnetic resonance imaging task. Of these participants, 23 completed the 3-year follow-up. None of the cue-induced region of interest activations predicted the amount of cannabis use at follow-up. However, cue-induced activation in the left striatum (putamen) significantly and independently predicted problem severity at follow-up ( p < 0.001) as assessed with the Cannabis Use Disorder Identification Test. Also, clinically dependent cannabis users at follow-up showed higher baseline activation at trend level in the left striatum compared with non-dependent users. This indicates that neural cue-reactivity in the dorsal striatum is an independent predictor of cannabis use-related problems. Given the relatively small sample size, these results are preliminary and should be replicated in larger samples of cannabis users.